Powder composite having improved water resistance and skin adhesion, and cosmetic composition comprising same
By applying the surface treatment of dextrin ester and high-fatty acid ester on cosmetic powder, combined with hydrophobizing treatment agents, the modified powder composite is formed, and the problem of insufficient water resistance and adhesion of the powder in sweat and sebum is solved, and the problem of insufficient water resistance and adhesion of the powder in sweat and sebum is achieved. Improves makeup durability and UV barrier effect.
Patent Information
- Application Number
- CN202480001346.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-28
- Filing Date
- 2024-01-03
- Publication Date
- 2024-12-13
AI Technical Summary
Powders in existing cosmetics are insufficient in water resistance and adhesion when facing sweat and sebum, resulting in poor makeup durability.
The powder is surface treated with a mixture of dextrin ester and higher fatty acid ester, combined with a hydrophobizing treatment agent to form a modified powder composite to improve water resistance and skin adhesion.
It significantly improves the water resistance of the powder to sweat and sebum, prevents darkening, while providing excellent UV barrier ability and makeup endurance.
Smart Images

Figure BDA0004939137670000081 
Figure BDA0004939137670000091 
Figure BDA0004939137670000101
Abstract
Description
Technical Field
[0001] The present invention relates to a powder composite having improved water resistance and skin adhesion and a cosmetic composition comprising the same. Background Art
[0002] As is known to all, cosmetics usually contain various powders such as coloring pigments, body pigments and white pigments, which play an important role in makeup and beauty by providing effects such as adding color tones and compensating for skin defects. However, existing cosmetics are easily removed by sweat or sebum, etc., so there is a problem of poor makeup durability.
[0003] In order to solve the above-mentioned problems, a method of improving water resistance by treating the surface of powder contained in cosmetics with higher fatty acids, higher alcohols, etc. to make it hydrophobic has been attempted.
[0004] However, these powders have limitations in improving water resistance and also have disadvantages such as poor adhesion to the skin and makeup durability when applied to cosmetics. Summary of the invention
[0005] Problem that the invention aims to solve
[0006] The present invention aims to solve the above problems, and its object is to provide a powder composite having improved water resistance and skin adhesion and a cosmetic composition comprising the same.
[0007] The technical problems of the present invention are not limited to the technical problems described above. Through the following description, technicians in this field can clearly understand other technical problems not mentioned.
[0008] Means used to solve problems
[0009] According to one embodiment of the present invention, a powder composite is provided, which may include: powder; and a modifier for treating the surface of the powder, wherein the modifier may include a mixture of dextrin ester and higher fatty acid ester.
[0010] In addition, the dextrin ester may include at least one selected from the group consisting of dextrin palmitate, dextrin palmitate / hexyldecanoate, dextrin palmitate / ethylhexanoate, dextrin myristate, dextrin behenate, dextrin stearate, and dextrin isostearate, and the higher fatty acid ester may include at least one selected from the group consisting of isopropyl titanium triisostearate, sorbitan triisostearate, trimethylolpropane triisostearate, oleyl stearate, pentaerythrityl stearate, glyceryl stearate, and isostearate. At least one of the group consisting of hexyldecyl stearate and hexyldecyl stearate.
[0011] In addition, the weight ratio of the above-mentioned modifier to the above-mentioned powder can be 1:3.5 to 35.
[0012] In addition, the weight ratio of the dextrin ester to the higher fatty acid ester may be 1:0.5 to 3.
[0013] In addition, the above-mentioned powder may include at least one selected from the group consisting of zinc oxide, titanium dioxide, iron oxide, nylon, zirconium oxide, silicon dioxide, manganese oxide, aluminum oxide, cerium oxide, mica, silicon dioxide, mica, boron nitride, methyl methacrylate cross-linked polymer, polymethyl methacrylate, talc, kaolin, organic pigments, organic dyes and lakes.
[0014] Furthermore, the powder may be surface-treated with a hydrophobizing agent.
[0015] The hydrophobic treatment agent may include at least one selected from the group consisting of aluminum hydroxide, alkyl silane, alkyl titanate, organic silicon compound and fluorine compound.
[0016] In addition, the weight ratio of the hydrophobizing agent to the powder may be 1:19 to 99.
[0017] According to one embodiment of the present invention, a cosmetic composition including the above powder complex is provided.
[0018] In addition, the above cosmetic composition can be used to block ultraviolet rays.
[0019] According to an embodiment of the present invention, a composition for external application to skin including the powder complex is provided.
[0020] Effects of the Invention
[0021] The powder composite according to the present invention can improve water resistance to sweat, sebum, etc. by surface-treating the powder with a mixture of dextrin ester and higher fatty acid ester.
[0022] Furthermore, the powder composite according to the invention can prevent the darkening phenomenon by minimizing the absorption of sweat, sebum and the like.
[0023] In addition, the cosmetic composition according to the present invention includes a powder complex having improved water resistance, and thus can provide excellent ultraviolet shielding ability, skin adhesion, and makeup durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to fully understand the drawings used in the detailed description of the present invention, a brief description of each drawing is provided here.
[0025] Figure 1 The following are photographs showing the results of an experiment for evaluating adhesion.
[0026] Figure 2 These are SEM photographs of powders used in Examples and Comparative Examples.
[0027] Figure 3 The following are photographs showing the results of contact angle measurement experiments of powders used in Examples and Comparative Examples.
[0028] Figure 4 The following are photographs showing the contact angle measurement test results of Examples and Comparative Examples. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art to which the present disclosure belongs. Generally, the terms used in this specification are well known and commonly used in the art. Moreover, in the process of describing the embodiments of the present invention, when it is judged that the specific description of the relevant known structure or function hinders the understanding of the embodiments of the present invention, its detailed description is omitted. In addition, the embodiments of the present invention are described below, but the technical ideas of the present invention are not limited thereto or limited thereto, and can be variously implemented by those of ordinary skill in the technical field to which the present invention belongs by deforming it.
[0030] According to any, when a component is referred to as "comprising" an element, unless otherwise expressly provided, instead of excluding any other elements, this may mean that a component may further include other elements. In this specification, the term "and / or" includes any and all combinations of one or more associated listed items.
[0031] According to an embodiment of the present invention, a powder composite is provided. The powder composite according to the embodiment of the present invention comprises: a powder; and a modifier, wherein the powder may be surface-treated by the modifier.
[0032] The powder is a material used as a basis for a powder composite, and may include, for example, an extender pigment, a coloring pigment, a white pigment, a pearlescent pigment, or the like.
[0033] In an embodiment, the powder may include at least one selected from the group consisting of zinc oxide, titanium dioxide, iron oxide, nylon, zirconium oxide, silicon dioxide, manganese oxide, aluminum oxide, cerium oxide, mica, silicon dioxide, mica, boron nitride, methyl methacrylate cross-linked polymer, polymethyl methacrylate, talc, kaolin, organic pigments, organic dyes, and lakes. However, the present invention is not limited thereto.
[0034] For example, the powder may be zinc oxide or titanium dioxide. Zinc oxide or titanium dioxide is not absorbed by the skin but acts on the surface, has physical properties of reflecting and scattering ultraviolet rays, and can provide ultraviolet blocking power in the ultraviolet range of UVA (315nm to 400nm) and / or UVB (280nm to 320nm). Specifically, zinc oxide or titanium dioxide may have a diameter of 10nm to 1,000nm, but is not limited thereto.
[0035] In an embodiment, the powder may be a powder surface-treated with a hydrophobic treatment agent, which makes the powder hydrophobic, thereby minimizing the phenomenon of powder agglomeration and improving the adsorption force with the modifier.
[0036] In an embodiment, the hydrophobizing agent may include at least one selected from the group consisting of aluminum hydroxide, alkyl silane, alkyl titanate, organic silicon compound and fluorine compound, specifically, aluminum hydroxide or alkyl silane. However, the present invention is not limited thereto.
[0037] For example, the alkylsilane may include at least one selected from the group consisting of triethoxyoctylsilane, methyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, phenyltrimethoxysilane, and diphenyldiethoxysilane. However, the present invention is not limited thereto.
[0038] For example, the alkyl titanate may include isopropoxy titanium tristearate, triisopropoxy titanium isostearate, isopropoxy titanium tripalmitate, and isopropoxy titanium trimyristate, etc., the organosilicon compound may include dimethicone, methicone, dimethicone / methicone copolymer, acrylate / dimethicone copolymer, methicone cross-polymer, and dimethicone cross-polymer, etc., and the fluorine compound may include trifluoropropyl trimethoxysilane, trifluoropropyl triethoxysilane, and tridecafluorooctyl trimethoxysilane, etc. However, the present invention is not limited thereto.
[0039] In an embodiment, the weight ratio of the hydrophobizing agent to the powder may be 1:19 to 99, specifically, 1:20 to 90. When the weight ratio of the hydrophobizing agent to the powder is within the above range, the surface of the powder may be uniformly hydrophobized, and the water resistance of the powder may be the best. However, the present invention is not limited thereto.
[0040] In one embodiment, the content of the powder may be 80 wt % to 99.9 wt %, specifically 85 wt % to 99.9 wt %, more specifically 90 wt % to 99.9 wt %, based on the total weight of the powder composite, but the present invention is not limited thereto.
[0041] The modifier is a material treated on the surface of the powder, and may include a mixture of dextrin esters and higher fatty acid esters. The powder surface-treated with the mixture of the above two ingredients can not only improve the water resistance to sweat and sebum, etc., but also improve the formulation stability, ultraviolet blocking ability, skin adhesion and makeup durability when applied to cosmetics. In addition, the darkening phenomenon (i.e., the phenomenon that the cosmetics condense together due to sweat and sebum, thereby darkening the color of the makeup) can be minimized by inhibiting the absorption of sweat, sebum, etc. into the powder.
[0042] In an embodiment, the dextrin ester may include dextrin palmitate. However, the present invention is not limited thereto, and the dextrin ester may include various ingredients known in the art such as dextrin palmitate / hexyldecanoate, dextrin palmitate / ethylhexanoate, dextrin myristate, dextrin behenate, dextrin stearate, and dextrin isostearate.
[0043] In an embodiment, the higher fatty acid ester may include stearic acid ester. However, the present invention is not limited thereto, and the higher fatty acid ester may include various components known in the art such as oleic acid ester, linoleic acid ester, palmitic acid ester, lauric acid ester, and myristic acid ester.
[0044] For example, the higher fatty acid ester may include isopropyl titanium triisostearate. However, the present invention is not limited thereto, and the higher fatty acid ester may include various ingredients known in the art such as sorbitan triisostearate, trimethylolpropane triisostearate, oleyl stearate, pentaerythritol stearate, glyceryl stearate, and hexyldecyl stearate.
[0045] In an embodiment, the content of dextrin ester and higher fatty acid ester can be 0.1 wt % to 8.0 wt % each, specifically, 0.1 wt % to 5.0 wt % based on the total weight of the powder composite. If the content of dextrin ester or higher fatty acid ester is less than 0.1 wt %, skin adhesion and makeup durability may be reduced, and if the content is more than 8.0 wt %, the dispersibility and feel of the powder may be reduced. However, the present invention is not limited thereto.
[0046] In an embodiment, the weight ratio of the modifier to the powder may be 1:3.0 to 35, specifically, 1:3.5 to 35. When the weight ratio of the modifier to the powder is within the above range, the coating process may be uniformly performed on the surface of the powder, and the effects of water resistance of the powder may be maximized. However, the present invention is not limited thereto.
[0047] In an embodiment, the weight ratio of dextrin ester to higher fatty acid ester may be 1:0.5 to 3, specifically, 1:1 to 2. When the weight ratio of dextrin ester to higher fatty acid ester is within the above range, the skin adhesion and makeup durability of the powder may be improved. However, the present invention is not limited thereto.
[0048] In the embodiment, the powder subjected to the primary surface treatment with the hydrophobizing treatment can be subjected to the secondary surface treatment with the modifier. The powder composite subjected to the dual surface treatment with the hydrophobizing treatment agent and the modifier has excellent powder dispersibility and water resistance, and when applied to cosmetics, can maximize the UV blocking effect and skin adhesion.
[0049] In an embodiment, a hydrophobizing agent and / or a modifier may be treated on the surface of the powder using a powder coating method known in the art. For example, various coating methods such as a wet process in which the hydrophobizing agent and / or a modifier and the powder are dispersed in an appropriate solvent and stirred with a homogenizer and a dry process in which the powder hydrophobizing agent and / or a modifier are dissolved in a solvent and then sprayed onto the powder may be used.
[0050] According to an embodiment of the present invention, a cosmetic composition is provided. The cosmetic composition may include the powder composite. For example, the powder composite may include a powder surface-treated with a mixture of dextrin palmitate and isopropyl titanium triisostearate (e.g., a powder surface-treated once with zinc oxide, titanium dioxide, a hydrophobic treatment agent, etc.). Zinc oxide or titanium dioxide surface-treated with the mixture may provide excellent formulation stability, water resistance, UV blocking ability, makeup durability, skin adhesion, and feel of use.
[0051] In an embodiment, the content of the powder complex may be 1 wt % to 20 wt %, specifically 2 wt % to 20 wt %, and more specifically 5 wt % to 15 wt %, based on the total weight of the cosmetic composition. However, the present invention is not limited thereto.
[0052] In an embodiment, the cosmetic composition can be used to block ultraviolet rays. According to an embodiment, in addition to the powder compound, the cosmetic composition may further include a sunscreen. For example, the sunscreen may be a water-soluble and / or oil-soluble sunscreen. For example, the sunscreen may include triazine compounds, salicylate compounds, benzotriazole compounds, benzophenone compounds, dibenzoylmethane compounds, acrylate compounds, etc. However, the present invention is not limited thereto.
[0053] In an embodiment, the cosmetic composition may further include additives commonly used in the art within the scope that does not impair the effects of the present invention. For example, the cosmetic composition may further include a thickener, a pH adjuster, an isotonic agent, a surfactant, a stabilizer, a preservative, a preservative, a bactericide, a moisturizer, a barrier agent, an antioxidant, an organic pigment, an inorganic pigment, a fragrance, a vitamin, etc. Those skilled in the art can easily select the mixing amount of the above ingredients within the scope that does not impair the purpose and effects of the present invention.
[0054] In an embodiment, the cosmetic composition can be provided in a formulation commonly made in the art. For example, the cosmetic composition can be formulated as an oil dispersion formulation in which the powder complex is dispersed in an oil phase, a water dispersion formulation in which the powder complex is dispersed in an aqueous phase, an emulsion formulation of oil-in-water (O / W), water-in-oil (W / O), water-in-oil-in-water (W / O / W), and oil-in-water-in-oil (O / W / O) type, a solubilizing formulation, etc. However, the present invention is not limited thereto, and the cosmetic composition can also be provided in a formulation such as a solution, a suspension, an emulsion, a solid, a gel, an oil, a powder, a paste, or a foam aerosol.
[0055] In an embodiment, the cosmetic composition can be made into various products. For example, the cosmetic composition can be made into functional cosmetics such as nutrient cream, essence, and ampoule, or basic cosmetics such as lotion and emulsion. In addition, it can also be made into soap, detergent, cleansing cream, cleansing water, etc., or made into lipstick, lip balm, mascara, blush, shadow, highlight, base makeup, foundation, pressed powder, concealer, concealer cream and other cosmetics. In addition, it can also be made into shampoo, conditioner, conditioner, hair spray and other hair cleaning products. In addition, for example, it can also be made into products attached to the skin such as facial mask, hydrogel slimming patch, etc., or it can be made into products sprayed on the skin such as spray or aerosol.
[0056] In an embodiment, the composition may be a composition for external use on the skin. For example, the composition for external use on the skin may have a formulation such as a cream, a gel, a skin emulsion, a patch, or a spray.
[0057] In an embodiment, as a skin external preparation composition, ingredients commonly used in skin external preparations such as cosmetics or pharmaceuticals can be appropriately mixed as needed, for example, aqueous ingredients, oily ingredients, powder ingredients, alcohol, moisturizers, thickeners, sunscreens, whitening agents, preservatives, antioxidants, surfactants, spices, colorants, fatty substances, solvents, concentrates, gelling agents, softeners, foaming agents, aromatics, metal ion blocking agents, chelating agents, vitamins, various skin nutrients or combinations thereof. Those skilled in the art can easily select the mixing amount of the above-mentioned ingredients within the scope of not damaging the purpose and effect of the present invention.
[0058] Experimental example
[0059] The present invention is described in more detail below by way of examples, but the present invention is not limited thereto.
[0060] Preparation of Examples and Comparative Examples
[0061] (1) Preparation of Powder Composites of Preparation Examples 1 to 4
[0062] The powder composite was prepared using the ingredients listed in the following Table 1. The unit of the ingredient content in Table 1 is weight %.
[0063] Table 1
[0064]
[0065] The specific preparation method is as follows.
[0066] The powder was added to the reactor, and then the active solvent was added while stirring at 500 rpm to form a primary powder continuous phase activated to the weakly acidic region, and then the modifier was slowly added to the continuous phase activated by the cationic surface while stirring at 300 rpm to form a secondary powder continuous phase. After that, the powder and the modifier were subjected to an acid-base reaction at a temperature of 75° C. for 4 hours to allow the modifier to complex on the powder surface, and the surface-treated powder was filtered through a 3HP pulverizer and a 50-mesh screen to obtain the powder composites of Preparation Examples 1 to 4.
[0067] (2) Preparation of Example 1 and Comparative Examples 1 to 4
[0068] The cosmetic composition was prepared using the components listed in the following Table 2. The unit of the component content in Table 2 is weight %.
[0069] Specifically, Comparative Examples 1 and 2 are compositions comprising powder composites surface-treated with only one of dextrin palmitate and isopropyl titanium triisostearate, while Comparative Example 3 is a composition comprising a powder composite surface-treated with a modifier outside the scope of the embodiments, and Comparative Example 4 is a composition containing dextrin palmitate and isopropyl titanium triisostearate alone as oil phase components instead of modifiers.
[0070] Table 2
[0071]
[0072] The specific preparation method is as follows.
[0073] After adding the powder to the oil phase component at room temperature, it is placed in a homogenizing mixer (PRIMIX) and stirred to pre-disperse, and then when the powder is fully stirred into the oil phase component, the water phase component is slowly added to perform pre-emulsification. After that, all the aqueous components are added and the main emulsification is performed. After the main emulsification is completed, the cosmetic composition of the embodiment and the comparative example is completed after defoaming.
[0074] Experimental example
[0075] (1) Experimental Example 1: Evaluation of formulation stability
[0076] The stability of the formulations of the above embodiments and comparative examples was evaluated by viscosity measurement and shaking test. The results are shown in Table 3.
[0077] The experimental method is as follows: In the case of viscosity measurement, for the samples of the above Examples and Comparative Examples, the viscosity of the composition on the day of preparation and after storage for 1 month at each temperature (5°C, 25°C, 45°C) was measured using an LV-4 rotor at 6 rpm.
[0078] In the case of the shaking test, each of the samples of the above Examples and Comparative Examples was rotated in a centrifuge (Termostable IS-20R model) at a temperature of 25° C. and a speed of 5,000 rpm for 5 minutes, and then visually checked for phase separation.
[0079] Table 3
[0080]
[0081] The experimental results show that Example 1 does not seem to have any viscosity change at various temperatures and does not undergo phase separation, thus having very excellent formulation stability.
[0082] On the other hand, in Comparative Example 1 including titanium dioxide surface-treated with dextrin palmitate alone, the viscosity changed rapidly at each temperature, confirming that the formulation stability was slightly inferior.
[0083] In Comparative Example 2 including titanium dioxide surface-treated only with isopropyl titanium triisostearate, the viscosity changed drastically at low temperature and room temperature, and phase separation occurred after 1 month at high temperature, confirming poor formulation stability.
[0084] In addition, in Comparative Example 3 including titanium dioxide surface-treated with a modifier outside the range of Examples, the viscosity changed rapidly at each temperature, confirming that the formulation stability was somewhat poor.
[0085] In addition, in Comparative Example 4 containing dextrin palmitate and isopropyl titanium triisostearate as oil phase components instead of modifiers, phase separation occurred after 1 month at low temperature, room temperature and high temperature, and phase separation also occurred in the oscillation test, confirming that the stability of the preparation was very poor.
[0086] (2) Experimental Example 2: Evaluation of UV blocking ability and water resistance
[0087] The ultraviolet shielding ability and water resistance of the above-mentioned Examples and Comparative Examples were evaluated. The results are shown in Table 4.
[0088] The experimental method is as follows: In the case of ultraviolet blocking ability (SPF), samples of Examples and Comparative Examples were respectively applied on HD-6 plates and evaluated using an SPF analyzer (UV-2000) after 15 minutes.
[0089] In addition, in the case of water resistance, the samples of the examples and comparative examples were coated on HD-6 plates, and after 15 minutes, they were attached to the bottom of a 1L beaker, 600 ml of 30°C tap water was added, and then the samples were mixed at 180 rpm using an AGI stirrer for 30 minutes. After drying for 30 minutes, the SPF values before and after the water resistance test and the integrated values of the absorbance at 290 nm to 400 nm were compared.
[0090] Table 4
[0091]
[0092] The experimental results confirmed that the SPF and water resistance of Example 1 were measured to be very high values.
[0093] On the other hand, it was confirmed that the SPF and water resistance of Comparative Examples 1 and 2 were measured as very low values.
[0094] In addition, in Comparative Example 3, it was confirmed that the measured SPF value was significantly low and thus could not be used as a sunscreen, and the measured water resistance value was also a very low value.
[0095] In addition, in Comparative Example 4, it was confirmed that although the SPF value was measured to be a high level, the water resistance value was measured to be a significantly low value.
[0096] (3) Experimental Example 3: Evaluation of makeup durability
[0097] The makeup durability of the above-mentioned Examples and Comparative Examples was evaluated. The results are shown in Table 5.
[0098] The experimental method is as follows. Take 0.05g of each sample of the embodiment and the comparative example, apply it on an artificial skin with an area of 3cm×3cm, spray squalene, which is a similar sebum component, once, and quantify the residual amount of each sample after 30 minutes at room temperature (25°C) using an image analysis program (Image J). The residual amount value is calculated based on the relative ratio of the residual amount of each sample compared with the control group without squalene spraying, and the measurement is performed three times and the average value is taken for evaluation.
[0099] Table 5
[0100] Classification Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Just after coating 1 1 1 1 1 Residue after injection 0.78 0.70 0.65 0.61 0.58
[0101] The experimental results showed that, in Example 1, even after spraying squalene, a large amount of the composition remained on the skin, and thus the makeup durability was very excellent.
[0102] On the other hand, in Comparative Examples 1 to 3, only a certain amount of the composition remained on the skin after spraying squalene, which shows that the makeup durability was poor.
[0103] In Comparative Example 4, a very small amount of the composition remained on the skin after spraying squalene, indicating that the makeup durability was very poor.
[0104] (4) Experimental Example 4: Adhesion and sticking evaluation
[0105] The adhesion and sticking of the above-mentioned examples and comparative examples were evaluated, and the results of Example 1 and Comparative Examples 1 to 4 are shown in the following pictures. Figure 1 (a) to (e) of .
[0106] The experimental method is as follows: The samples of the embodiment and the comparative example were coated into a size of 50 mm×50 mm, dried for 30 minutes, and then subjected to an adhesion test using 3M 610 adhesion test tape.
[0107] Reference Figure 1 (a), in Example 1, the states before and after the adhesion test were almost the same, and the composition was hardly attached to the tape, which shows that the adhesion to the skin was very excellent.
[0108] On the other hand, refer to Figure 1 (b) and (c), in Comparative Examples 1 and 2, after the adhesion test, a larger amount of the composition adhered to the tape and was removed compared to Example 1, which shows that the adhesion to the skin is poor.
[0109] And, refer to Figure 1 (d) and (e), in Comparative Examples 3 and 4, a considerable amount of the composition adhered to the tape and was removed after the adhesion test, which shows that the adhesion to the skin is very poor.
[0110] (5) Experimental Example 5: Observation of powder composite using SEM
[0111] The powders used in Example 1 and Comparative Example 4 were photographed using a scanning electron microscope (SEM). Figure 2 shown. Specifically, Figure 2 (a) is a SEM photograph of the powder used in Example 1, Figure 2 (b) is a SEM photograph of the powder used in Comparative Example 4.
[0112] Reference Figure 2 In the case of the powder used in Example 1, it can be seen that the mixture of dextrin palmitate and isopropyl titanium triisostearate was densely and uniformly processed on the surface of titanium dioxide.
[0113] (6) Experimental Example 6: Evaluation of Usage Experience
[0114] In order to evaluate the use experience of the above-mentioned embodiments and comparative examples, 30 evaluators aged 20 to 40 were asked to evaluate items such as moisturizing feel, refreshing feel, adhesion, spreadability, softness, finishing effect and durability. The results are shown in Table 6.
[0115] The experimental method is as follows. After applying the samples of the above-mentioned embodiments and comparative examples to the skin of the evaluator, the feeling of each evaluation item is evaluated on a five-level evaluation scale, with 5 points as the full score and 1 point as the level increases. As for the feeling of use, the value after excluding the deviation after calculating the average of the total score is evaluated.
[0116] Table 6
[0117]
[0118]
[0119] The experimental results showed that Example 1 had high scores in terms of moisturizing feeling, refreshing feeling, adhesion, spreadability, softness, finishing effect, and durability, which indicated that it provided a very excellent feeling during use.
[0120] On the other hand, the scores of Comparative Example 1 were low compared with Example 1 in terms of moisturizing feeling, adhesion, spreadability, finishing property, and durability. In particular, the scores of refreshing feeling and softness were very low, indicating that the feeling during use was poor.
[0121] In addition, the scores of Comparative Example 2 were low compared with Example 1 in the moisturizing feeling and refreshing feeling items. In particular, the scores of the adhesion, spreadability, softness, finishing property and durability items were very low, which shows that the feeling during use was poor.
[0122] In addition, the scores of the refreshing feeling and spreadability items of Comparative Example 3 were low compared with those of Example 1, and the scores of the moisturizing feeling, adhesion, softness, finishing property, and durability items were very low, indicating that the feeling during use was poor.
[0123] In addition, the score of the softness item of Comparative Example 4 was low compared with Example 1, and the scores of moisturizing feeling, adhesion, fresh feeling, spreadability, finishing property and durability were very low, which shows that the feeling during use was poor.
[0124] (7) Experimental Example 7: Contact Angle Measurement
[0125] In order to compare the hydrophobicity of each coated substrate of the above-mentioned Examples and Comparative Examples, the contact angle was measured, and the results are shown in FIG. Figure 3 , Figure 4and Table 7. The contact angle is measured to compare the changes in phase and physical properties. It is a value that can predict the change in surface free energy, that is, the change in surface tension. The larger the contact angle, the higher the hydrophobicity can be evaluated.
[0126] The specific experimental method is as follows. The powder samples used in the embodiment and the comparative example were pelletized using a KBr pelletizer from PIKE. Then, the granular powder was placed on a glass slide and a contact angle meter (DSA25 from Kruss) was used to measure the contact angle. The purified water was dripped into a drop shape and then slowly contacted with the particles to form a droplet. After 1 minute, the contact angle between the droplet and the powder surface was measured using the built-in camera of the contact angle meter. The contact angle measurement results of the powders used in Example 1 and Comparative Examples 1 to 4 are shown in the table below. Figure 3 (a) to (e) of .
[0127] In addition, in order to evaluate the hydrophobicity when the powder is applied to a W / O type preparation, the contact angles of the samples of the examples and comparative examples were also measured. The contact angle measurement results of Example 1 and Comparative Examples 1 to 4 are shown in order. Figure 4 (a) to (e) of .
[0128] Table 7
[0129]
[0130] The experimental results show that the contact angle of the powder used in Example 1 was measured to be higher than the contact angles of the powders used in Comparative Examples 1 to 4, from which it can be seen that the powder has very excellent hydrophobicity.
[0131] In addition, the contact angle of Example 1 in which the powder was applied to the W / O type was also measured to be higher than the contact angles of Comparative Examples 1 to 4, which shows that the water resistance to sweat, sebum, etc. and the makeup durability are improved by using a powder having excellent hydrophobicity.
[0132] (8) Experimental Example 8: Measurement of Darkening Improvement Effect
[0133] The darkening improvement effect of each coated substrate when the powders of the above-mentioned Examples and Comparative Examples were applied to foundation preparations was evaluated, and the results are shown in Table 8.
[0134] The specific experimental method is as follows. Take 0.5g of the samples of the above-mentioned embodiments and comparative examples respectively, apply them on artificial skin in an area of 3cm×3cm, and compare the colors immediately after application and 3 hours after application at 25°C with the naked eye to confirm the degree of darkening. As an equipment, a colorimeter (KONICAMINOLTA, SPECTRO PHOTO METER CM-600d) is used for measurement, and the specific measurement method is as follows. Measure the L value (lightness), a value (red-green chromaticity) and b value (yellow-blue chromaticity) (the average value of three measurements) after 3 hours at 25°C, and then use the formula [ΔE=√(ΔL*) 2 +(Δa*) 2 +(Δb*) 2 ] Calculate the ΔE value. In the above formula, ΔL*=L2-L1, Δa*=a2-a1, Δb*=b2-b1, L1, a1 and b1 are the L, a and b values of the initial sample just after coating, and L2, a2 and b2 are the L, a and b values of the sample after 3 hours.
[0135] Table 8
[0136]
[0137] As an experimental result, in the case of Example 1, the measured color difference was 0.21, confirming that the darkening phenomenon was significantly suppressed.
[0138] On the other hand, in the case of Comparative Examples 1 to 4, the measured color differences were all 0.39 or more, which shows that the darkening phenomenon occurred.
[0139] Although specific parts of the present invention have been described in detail, it should be understood by those skilled in the art that the above specific techniques are provided to illustrate preferred embodiments for illustrative purposes and should not be understood to limit the scope of the present invention. Therefore, the essential scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A powder composite, characterized in that: include: powder; and Modifier, used to treat the surface of the above powder, The above-mentioned modifier includes a mixture of dextrin ester and higher fatty acid ester.
2. The powder composite according to claim 1, characterized in that The dextrin ester includes at least one selected from the group consisting of dextrin palmitate, dextrin palmitate / hexyldecanoate, dextrin palmitate / ethylhexanoate, dextrin myristate, dextrin behenate, dextrin stearate and dextrin isostearate, The higher fatty acid ester includes at least one selected from the group consisting of isopropyl titanium triisostearate, sorbitan triisostearate, trimethylolpropane triisostearate, oleyl stearate, pentaerythritol stearate, glyceryl stearate and hexyldecyl stearate.
3. The powder composite according to claim 1, characterized in that The weight ratio of the above-mentioned modifier to the above-mentioned powder is 1:3.5 to 35.
4. The powder composite according to claim 1, characterized in that The weight ratio of the dextrin ester to the higher fatty acid ester is 1:0.5 to 3.
5. The powder composite according to claim 1, characterized in that The powder includes at least one selected from the group consisting of zinc oxide, titanium dioxide, iron oxide, nylon, zirconium oxide, silicon dioxide, manganese oxide, aluminum oxide, cerium oxide, mica, silicon dioxide, mica, boron nitride, methyl methacrylate cross-linked polymer, polymethyl methacrylate, talc, kaolin, organic pigments, organic dyes and lakes.
6. The powder composite according to claim 1, characterized in that The above-mentioned powder is a powder surface-treated with a hydrophobizing agent.
7. The powder composite according to claim 6, characterized in that The hydrophobizing agent includes at least one selected from the group consisting of aluminum hydroxide, alkyl silane, alkyl titanate, organic silicon compound and fluorine compound.
8. The powder composite according to claim 6, characterized in that The weight ratio of the hydrophobizing agent to the powder is 1:19 to 99.
9. A cosmetic composition, characterized in that A powder composite comprising the powder composite of any one of claims 1 to 8.
10. The cosmetic composition according to claim 9, characterized in that The cosmetic composition is used for shielding ultraviolet rays.
11. A composition for external use on skin, characterized in that: A powder composite comprising the powder composite of any one of claims 1 to 8.
